Solvent-controlled plasmon-assisted surface catalysis reaction of 4-aminothiophenol dimerizing to p, p'-dimercaptoazobenzene on Ag nanoparticles. Issue 4 (April 2019) - Liu, Yu; Yang, Dongqi; Zhao, Yuanchun; Yang, Yanqiu; Wu, Shiwei; Wang, Jing; Xia, Lixin; Song, Peng
Abstract: A large number of literatures have investigated the selective photocatalytic reaction of 4-aminothiophenol (PATP) to p, p'-dimercaptoazobenzene (DMAB). Most of them mainly study the contribution of substrate, excitation wavelength, exposure time, pH and added cations to plasmon-assisted surface catalytic reactions. However, we mainly study focuses on the effects of solvents on the dimerization of PATP to DMAB under the action of Ag nanoparticles (NPs). In experiments, a variety of diols was selected as solvents for the probe molecule PATP, and power-dependent SERS spectra were obtained at an excitation wavelength of 532 nm. From the laser-dependent SERS spectrum, we found that the characteristic peak enhancement effect of the product DMAB in different solvents is significantly different. That is, different solvents could regulate the rate at which DMAB is produced from PATP. Based on the experimental results, we further explored how different diol solvents regulate the response of PATP to DMAB. Our conclusion is that the solvent in the system can quickly capture the hot electrons generated by the decay of the plasmon, so that the remaining holes can oxidize PATP to form DMAB. The ability to trap hot electrons is different due to the difference in the position of the functional groups in the solvent, so that the photocatalytic reaction rate of the hole-oxidized PATP is different. The ability to capture electrons varies depending on the position of the functional groups in the solvent, so the oxidation rate of the photocatalytic reaction is also different. This work not only deepens our understanding of the mechanism of hole-driven surface catalysis oxidation reaction, but also provides a convenient method for regulating the rate of catalytic oxidation.